COMPETENCE APPROACH AND THE TRADITIONAL VIEW ON HIGHER EDUCATION - Evgeniy A. Korchagin; Rais S. Safin (Высшее образование в России)
Within the discussion about the competence approach in higher education the article highlights the issues of goal-setting and diagnosing of higher professional education purposes. By the comparison of traditional and competence-based approaches to the formulation of the obj ectives of higher vocational education the authors come to a conclusion of insufficient methodological support of competence-based approach in educational practice. The main objective of the competence-based approach lies in a personal development of a student, which means the formation of stable systematic knowledge, skills and then, on this basis, the formation of competences. However, in the educational practice, this main purpose is usually not achieved for the reasons of insufficiency of training time and the lack of methodological support, and faculty unpreparedness. The types of graduates' professional activity and the main options of training activities are discussed. Within the framework of standardization of higher education the creative possibilities of competence-based approach in the development of student personality are limited with the education level of trainers and do not match the essence of research activities, which master degree graduates and postgraduate students are prepared to. The boundaries of the applicability of the competences and competence-based approach in higher education today are not clearly defined, since the competences and the competence approach are not defined themselves.